Sport-specific training induced adaptations in postural control and their relationship with athletic performance - Zemková, Erika; Kováčiková, Zuzana (Frontiers in Human Neuroscience, 2023)
Effects of various exercise programs on postural balance control in athletes and their underlying physiological mechanisms have been extensively investigated. However, little is known regarding how challenging sport-specific conditions contribute to the improvement of body balance and to what extent these changes may be explained by sensorimotor and/or neuromuscular function adaptations. Analysis of the literature could provide useful information on the interpretation of changes in postural sway variables in response to long-term sport-specific training and their association with performance measures. Therefore, the aim of this scoping review was (1) to analyze the literature investigating postural control adaptations induced by sport-specific training and their relationship with measures of athletic performance, and (2) to identify gaps in the existing research and to propose suggestions for future studies. A literature search conducted with Scopus, Web of Science, MEDLINE and Cochrane Library was completed by Elsevier, SpringerLink and Google Scholar with no date restrictions. Overall, 126 articles were eligible for inclusion. However, the association between variables of postural balance control and measures of sport-specific performance was investigated in only 14 of the articles. A relationship between static and/or dynamic balance and criterion measures of athletic performance was revealed in shooting, archery, golf, baseball, ice-hockey, tennis, and snowboarding. This may be ascribed to improved ability of athletes to perform postural adjustments in highly balanced task demands. However, the extent to which sport-specific exercises contribute to their superior postural stability is unknown. Although there is a good deal of evidence supporting neurophysiological adaptations in postural balance control induced by body conditioning exercises, little effort has been made to explain balance adaptations induced by sport-specific exercises and their effects on athletic performance. While an enhancement in athletic performance is often attributed to an improvement of neuromuscular functions induced by sport-specific balance exercises, it can be equally well ascribed to their improvement by general body conditioning exercises. Therefore, the relevant experiments have yet to be conducted to investigate the relative contributions of each of these exercises to improving athletic performance.